Chemical and biological evaluation of rubber (Hevea brasiliensis) seed meal - Nwokolo E; Akpakunam M
Fresh, shelled rubber seed meal was solvent extracted for chemical characterisation of the ether extract fraction. Routine tests included saponification number, iodine value, peroxide value and free fatty acid contents. For detection and quantification of component fatty acids, the ether extract fraction was acid hydrolysed (4 hours), extracted with chloroform and analysed in a Varian model 3700 Gas Chromatograph using a stationary phase of 20;Carbowax deactivated with 1;H3PO4. Proximate analysis of defatted rubber seed meal was followed by atomic absorption spectrophotometry to quantify component minerals. From a short duration experiment involving feeding mineral-free reference diets as well as the test ingredients, availability of minerals in rubber seed meal was determined. Finally, defatted rubber seed meal was incorporated at levels of 10;, 15;and 20;into diets of three-week old broiler chicks for a 14 day feeding trial. A summary of the results of chemical and biological evaluation of rubber seed meal with reference to its suitability as a major protein source in poultry nutrition is provided.
Keywords: Amino acids; Biological evaluation; Chemical evaluation; Fatty acid content; Nutritional value; Poultrynutrition; Rubber seed meal